The Role of Corporate Social Responsibility in Flood Mitigation among the Listed Insurance Companies in Malaysia - Ramakrishnan, Suresh; Hishan, Sanil S.; Shahabuddin, Abu Saim Mohammad; Kanjanapathy, Malini (International Review of Management and Marketing, 2016)
Rapid industrialisation in the developing countries has contributed to an increase in natural disasters. Rise in the losses due to disasters is an indicator of non-sustainable development. Although in Malaysia the natural forces have been mainly liable for the natural disasters in the past, in recent times human intervention in nature is worsening the flood hazards in particular. As we move closer to the year 2020, the country is expected to face serious challenges in flood management. The recent flood situation is an example of the increase in the magnitude of the flood disaster. In this scenario, it is imperative to have a holistic plan to face this challenge. The role of the corporate social responsibility (CSR) in flood mitigation is one area which needs to be researched as private sector can play a key role in flood mitigation. This research involved a content analysis of company websites of the listed insurance companies in Malaysia to examine the extent to which these companies get themselves involved in the CSR programs related to flood relief and mitigation. The results showed that majority of the insurance companies that have the flood related CSR initiative is foreign owned. Furthermore, these companies have an institutionalized approached towards CSR. The result also shows that local insurance companies do not contribute much in terms of the flood mitigation related CSR programs. Based on the result of the website study we can conclude that the foreign insurance companies involve themselves in flood mitigation related CSR programs. However, the local insurance companies need to step up their efforts in terms of CSR programs related to the flood relief and mitigation. Keywords: Corporate Social Responsibility, Communication, Insurance, Flood Mitigation, Disaster management, Malaysia JEL Classifications: D83, M14